Perancangan Peta Rute Wisata sebagai Alat Pemasaran bagi Desa Wisata di Subang Selatan - Katik Rajo Endah, Muhammad Iqbal; Saputro, Restu Jati; Syah, Firman; Mubarak, Fauzi; Setyawan, Heri; Wardhani, Annisa (J-Dinamika : Jurnal Pengabdian Masyarakat, 2024)
Southern Subang has the potential for various tourist attractions, including six tourism villages, namely Cipancar Tourism Village in Serangpanjang District, Dayeuh Kolot Tourism Village and Sukamandi Tourism Village in Sagalaherang District, Bunihayu Tourism Village and Tambak Mekar Tourism Village in Jalan Cagak District, and Cirangkong Tourism Village in Cijambe District. Community Based Science and Technology Implementation Service (PPIBM) of MICE Study Program, Politeknik Negeri Jakarta carries out the design and preparation of tourist route maps which can be used as a marketing tool for tourism villages in Southern Subang. The series of PPIBM activities are conducting secondary studies, carrying out workshops and surveys, designing tourist routes and socializing tourist route maps. The Tourism Awareness Group (Pokdarwis) and village officials were involved in implementing PPIBM to gain an understanding of how to design a tourist route. The output of this community service project is a tourist route map in the form of a pamphlet, the copyright for which has been registered, with the goal of enhancing tourist visits and length of stay in Southern Subang.